Current practice patterns and training project of orthodontic specialists in Taiwan in 2020 - Julia Yu-Fong Chang; Shih-Jaw Tsai; Tzu-Chiang Lin; Ling-Hsia Wang; Feng-Chou Cheng; Chun-Pin Chiang (Elsevier, 2021)
Background/purpose: There were 661 board-certified orthodontic specialists in Taiwan in 2020. This study reported the current practice patterns and training project of orthodontic specialist in Taiwan. Materials and methods: This study exploited the secondary data analysis and interview to survey the current practice patterns and training project of orthodontic specialists in Taiwan. Results: Of the 661 orthodontic specialists, there were 84 registered in the medical centers, 44 in the regional hospitals, 7 in the district hospitals, and 526 in the dental clinics, respectively. There were 20 orthodontic specialist training institutions (15 medical centers, 3 regional hospitals, one district hospital, and one dental clinic) that had 218 dentists in orthodontic departments of training institutions and a training capacity of 51 dentists. Of the 20 orthodontic specialist training institutions in Taiwan in 2020, 12 were located in the northern, 4 in the central, and 4 in the southern regions of Taiwan. Moreover, we found none of the training institutions in the eastern and offshore island regions of Taiwan and the number of the orthodontic specialists did increase along with the population and the number of the practicing dentists. Conclusion: There are three major orthodontic specialist occupation problems in Taiwan: a surplus of the orthodontic specialists in the near future, an uneven distribution of the orthodontic specialists, and a concentration of the orthodontic specialists in the metropolitan areas of the municipalities. Therefore, we suggest that the government and relevant professional groups should propose solutions for these problems as soon as possible.